Childbirth Related Post-traumatic Stress Symptoms and Maternal Sleep Difficulties: Associations With Parenting Stress - Di Blasio, Paola; Camisasca, Elena; Miragoli, Sarah (Frontiers in Psychology, 2018)
In the literature, increasing evidence is showing the importance of sleep difficulties in the development or maintenance of posttraumatic stress (PTS) symptoms as well as the association between childbirth-related PTS symptoms and early maternal emotions and perceptions of their children. However, little is known regarding the effects of maternal sleep difficulties on parenting or about the mediational role of childbirth-related PTS symptoms in this association. The present study (pregnancy: T0; 1 month postpartum: T1; 3 months postpartum: T2) had two aims. The first one was to explore whether maternal sleep difficulties could contribute to the maintenance of PTS symptoms and whether PTS symptoms could contribute to the maintenance of maternal sleep difficulties. The second purpose was to explore, at 3 months (T2), the associations among childbirth-related PTS symptoms, maternal sleep difficulties, and the three dimensions of parenting stress (parental distress, parent–child dysfunctional interaction, and difficult child) by examining the mediational role of both maternal sleep difficulties and childbirth-related PTS symptoms. Self-report questionnaires were administered to 95 women at different times (T0, T1, and T2). Mediational results confirmed the bidirectional effects between maternal sleep difficulties and PTS symptoms and their reciprocal role of maintenance of symptoms. Moreover, at 3 months postpartum (T2), sleep difficulties mediated the association between PTS symptoms and the three dimensions of maternal parenting stress, while PTS symptoms mediated the associations among maternal sleep difficulties, parental distress, and difficult child dimensions of parenting stress. The study contributes to the understanding of the maintenance factors of childbirth-related PTS symptoms and of the relationships among PTS symptoms, maternal sleep difficulties, and parenting stress